Micro-CT assessment of two different endodontic preparation systems - de Moura-Netto, Cacio; Palo, Renato Miotto [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Pameijer, Cornelis Hans; da Silva Bardauil, Marcia Regina Ramalho (FapUNIFESP (SciELO), 2013)
The aim of this study was to compare two endodontic preparation systems using micro-CT analysis. Twenty-four one-rooted mandibular premolars were selected and randomly assigned to two groups. The samples (n = 12) of Group 1 were prepared using the ProTaper Universal rotary system, while Group 2 (n = 12) was prepared using the EndoEZE AET system complemented by manual apical preparation with K-type hand files up to #30. A 2.5% sodium hypochlorite solution was used in both groups for irrigating. Both groups were scanned by highresolution microcomputed tomography before and after preparation (SkyScan 1172, SkyScan, Kontich, Belgium). The root canal volume and surface area was measured before and after preparation, and the differences were calculated and analyzed for statistically significant differences using ANOVA complemented by the Tukey test (p < 0.05). The results showed no statistically significant differences between the mean volumes of dentin removal by the two systems. However, the EndoEZE AET system presented a significantly greater mean surface area compared to the ProTaper system (p < 0.05). The EndoEZE AET system enabled preparation of a greater root canal surface area when compared to the ProTaper Universal system. There seemed to be no difference in dentin volume loss between the two systems used.
Keywords: Dental pulp cavity; Endodontics; Root canal therapy; dental alloy; nickel; stainless steel; titanium; titanium nickelide; chemistry; comparative study; dental equipment; dentin; endodontics; equipment design; human; instrumentation; methodology; micro-computed tomography; nonparametric test; radiography; randomization; reproducibility; surface property; tooth pulp; Dental Alloys; Dental Instruments; Dental Pulp Cavity; Dentin; Equipment Design; Humans; Nickel; Random Allocation; Reproducibility of Results; Root Canal Preparation; Stainless Steel; Statistics, Nonparametric; Surface Properties; Titanium; X-Ray Microtomography